Does bariatric surgery improve cardiac autonomic modulation assessed by heart rate variability? A systematic review - Benjamim, Cicero Jonas R. [UNESP]; Pontes, Yasmim Mota de M.; de Sousa Junior, Francisco Welington; Porto, Andrey Alves [UNESP]; Bueno Júnior, Carlos Roberto; Marcelino da Silva, Amanda A.; Ferro Cavalcante, Taisy C.; Garner, David M.; Valenti, Vitor E. [UNESP] (Elsevier, 2021)
Our study aimed to explore the influence of bariatric surgery (BS) on heart rate (HR) variability (HRV) through a systematic review. Manuscripts were selected based on electronic searches of the MEDLINE, EMBASE, and CINAHL databases from the inception of each database up to year 2020, and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Searching of these studies was systematized using the Population Intervention Comparison Outcome Study Design strategy. We selected randomized and nonrandomized controlled trials and cohorts from prospective studies that reported the influence of BS on HRV. We assessed the quality rating using the Black and Downs questionnaire. Following the screening and eligibility stages, 14 studies were included in the review. All studies agreed that BS promotes an increase in parasympathetic HR control and HRV and a decrease in HR. Yet the literature does not provide evidence that these outcomes are directly caused by the surgical procedure. There is limited evidence to support that patients with type 2 diabetes have greater improvement in HRV as an interim measure, to individuals without. The decrease in insulin resistance was correlated with the increase in HRV in some studies, but, other studies are unsupportive of this outcome. Improvements in 2 metabolic parameters (e.g., leptin, N-terminal pro B–type natriuretic peptide) were connected with superior increases in HRV. This review demonstrated that BS promotes an increase in HRV, indicating improved autonomic control of HR.
Keywords: Bariatric surgery; Cardiovascular physiology; Heart rate variability; Metabolic diseases; Obesity; Rehabilitation